Shared genetic contribution to ischemic stroke and Alzheimer's disease. Issue 5 (30th March 2016) - Traylor, Matthew; Adib‐Samii, Poneh; Harold, Denise; ,; Dichgans, Martin; Williams, Julie; Lewis, Cathryn M.; Markus, Hugh S.; ,
Abstract : Objective: Increasing evidence suggests epidemiological and pathological links between Alzheimer's disease (AD) and ischemic stroke (IS). We investigated the evidence that shared genetic factors underpin the two diseases. Methods: Using genome‐wide association study (GWAS) data from METASTROKE + (15, 916 IS cases and 68, 826 controls) and the International Genomics of Alzheimer's Project (IGAP; 17, 008 AD cases and 37, 154 controls), we evaluated known associations with AD and IS. On the subset of data for which we could obtain compatible genotype‐level data (4, 610 IS cases, 1, 281 AD cases, and 14, 320 controls), we estimated the genome‐wide genetic correlation (rG) between AD and IS, and the three subtypes (cardioembolic, small vessel, and large vessel), using genome‐wide single‐nucleotide polymorphism (SNP) data. We then performed a meta‐analysis and pathway analysis in the combined AD and small vessel stroke data sets to identify the SNPs and molecular pathways through which disease risk may be conferred. Results: We found evidence of a shared genetic contribution between AD and small vessel stroke (rG [standard error] = 0.37 [0.17]; p  = 0.011). Conversely, there was no evidence to support shared genetic factors in AD and IS overall or with the other stroke subtypes. Of the known GWAS associations with IS or AD, none reached significance for association with the other trait (or stroke subtypes). A meta‐analysis of AD IGAP and METASTROKE + small vessel stroke GWAS data highlighted a region (ATP5H/KCTD2/ICT1) associated with both diseases ( p  = 1.8 × 10 −8 ). A pathway analysis identified four associated pathways involving cholesterol transport and immune response. Interpretation: Our findings indicate shared genetic susceptibility to AD and small vessel stroke and highlight potential causal pathways and loci. Ann Neurol 2016;79:739–747